Radiation-induced grafting of styrene onto poly(tetrafluoroethylene) (PTFE) films. I. Effect of grafting conditions and properties of the grafted films - Nasef, Mohamed Mahmoud; Saidi, Hamdani; Dessouki, Ahmed Mokhtar; EI-Nesr, Eman Mohamed (2000)
Radiation-induced grafting of styrene onto poly(tetra¯uoroethylene) (PTFE) films was studied by a simultaneous irradiation technique. Grafting was carried out using g-radiation from a 60Co source at dose rates of 1.32±15.0kGyhÿ1 at room temperature. The effects of type of diluent, dose rate, irradiation dose, and the initial monomer concentration in the grafting solution on the degree of grafting were investigated. The degree of grafting was found to be strongly dependent upon the grafting conditions. The dependence of the initial rate of grafting on the dose rate and the initial monomer concentration in the grafting solution was found to be in the order of 0.6 and 1.7, respectively. The chemical structure and the crystallinity of the grafted PTFE films were studied by means of Fouriertransform infrared, (FTIR), electron spectroscopy for chemical analysis (ESCA) and X-ray diffractometry (XRD).